Effect of environmental sulfur on the structure of alumina scales formed on Ni-base alloys. (15th September 2015) - Liu, Xu; Bonifacio, Cecile; Yang, Judith C.; Ercius, Peter; Gleeson, Brian
Abstract: Short-term oxidation exposures of an alumina-scale forming γ′-Ni3 Al-based model alloy in air and O2 + 0.1%SO2 at 900 °C revealed that the presence of sulfur can affect the kinetic competition between the θ and α structural isomorphs of Al2 O3 . After 2 h exposure, metastable θ-Al2 O3 growth predominated in air alone; whereas, a much larger percentage of stable α-Al2 O3 formed during oxidation in O2 + 0.1%SO2 . This promotion of α-Al2 O3 establishment was due to sulfur enrichment on the alloy surface, which occurred even when samples were exposed to O2 + 0.1%SO2 in a low-temperature, pre-test position (∼150 °C), i.e., prior to insertion into the hot zone. It was determined from XPS measurements that the sulfur was mainly in the S 6+ valence state and, correspondingly, in the form of NiSO4 . Cross-sectional scanning transmission electron microscopy (STEM) using energy-dispersive X-ray spectroscopy (EDS) corroborated the XPS results by detecting that a ∼20 nm zone of sulfur enrichment within the surface region of a ∼90 nm oxygen-rich layer formed during the pre-test exposure. A systematic explanation for this intriguing observation of sulfur promoting α-Al2 O3 establishment is provided from the perspective of kinetics competition between θ and α. This explanation was supported by kinetic calculations and complementary tests in a low p O 2 atmosphere.